Fatores biopsicossociais associados ao estado de incapacidade após acidente vascular cerebral: análise exploratória baseada na classificação internacional de funcionalidade, incapacidade e saúde - Santos, Heyriane Martins dos (2021)
Introduction: According to the International Classification of Functioning, Disability and Health (ICF), the environment is associated with the state of human disability and functionality, however, few studies seek to analyze the influence of the environment on disability after stroke. Objectives: Study 1- identify how environmental barriers and facilitators relate to disability after stroke. Study 2-identify the main biopsychosocial predictors associated with the level of disability after stroke according to the ICF biopsychosocial model. Methods: Both studies are exploratory cross-sectional analytical, in which individuals with chronic stroke were evaluated. Disability was considered the dependent variable, being assessed by the World Health Disability Assessment Schedule (WHODAS-2.0). In Study 1, the independent variable was the environment, assessed using the Measure of the Quality of the Environment (MQE). Multiple linear regression was used to estimate the impact of the environment on disability after stroke. In Study 2, the independent variables were determined using the ICF biopsychosocial model: the personal factors considered were: age, sex and income. For bodily functions, the emotional function (Geriatric Depression Scale (GDS)) was considered, and whether the dominant upper limb was affected by stroke. For the activity and participation component, satisfaction in carrying out activities and participation, locomotion, and manual skill were considered, assessed by Satispart Stroke (SATIS-Stroke), Locomotion ability for adults (ABILOCO) and manual ability for adults with upper limb impairment (ABILHAND), respectively; in addition to considering the return to work. For the environmental factors, the environmental facilitators and obstacles that were assessed by the MQE were considered. Binary logistic regression for likelihood ratio was used. Results: Study 1- the main barriers were those related to the physical environment. It was observed that the barrier environment was a predictor of general disability [F(1.73) = 4.24; R2=0.06; β = -0.23; t = -2.06; p=0.04] and predictor of participation [F(1.73) = 10.45; R2=0.13; β = -0.35; t = -3.23; p = 0.01]. Environmental enablers did not correlate with disability. Study 2 -It identified that satisfaction in activities and participation (OR = 0.17; 95%CI 0.03-0.80, p=0.02) and income (OR = 1.96; 95%CI 1.03-3.71, p=0.03) proved to be independent predictors of disability. Conclusion: The physical environment was identified as a barrier, being a predictor of disability after a stroke. When performing the analysis based on the biopsychosocial model, the environment continued to be a factor associated with disability, however, related to the lack of access to health services. Low income and decreased satisfaction in carrying out activities and participation were also factors associated with disability after stroke. Variables related to bodily functions were not related to disability.